2016
DOI: 10.1002/mnfr.201500830
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil regulates blood fatty acid composition and oxylipin levels in healthy humans: A comparison of young and older men

Abstract: Our study suggests that both young and older men experience the triglyceride-lowering benefits associated with fish oil supplements, but show differential responses in blood fatty acids. Additionally, fish oil promotes an improved oxylipin profile in both groups of men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…In this study we found that the change in the dietary EPA intake correlated with the proportion of DPA only in TG (data not shown). We also observed an increase in the proportion of DPA in the fatty fish group in TG (Table 4) which is supported by earlier studies reporting increased plasma DPA levels after fish oil treatment [25,39]. Furthermore, increased ALA intake has been previously reported to increase the proportion of DPA but not DHA in plasma lipid pools [12,34,35].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study we found that the change in the dietary EPA intake correlated with the proportion of DPA only in TG (data not shown). We also observed an increase in the proportion of DPA in the fatty fish group in TG (Table 4) which is supported by earlier studies reporting increased plasma DPA levels after fish oil treatment [25,39]. Furthermore, increased ALA intake has been previously reported to increase the proportion of DPA but not DHA in plasma lipid pools [12,34,35].…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that women have lower proportions of EPA [41], but higher proportions of DHA in PL, CE and EM [41,42]. Results regarding the effect of age on fatty acid composition in different lipid pools have been controversial [25,41]. Some studies have reported increased proportions of EPA and DHA in PL and EM with age, from 20-year-olds to over 60-year-olds [41,43] whereas Zulyniak et al [25] found greater increases in EPA and DHA contents in EM in young men (18e30 years) than in older men (60e74 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While metabolic rate remained unaffected by DHA supplementation, there was an increase in fatty acid oxidation and a simultaneous decrease in carbohydrate oxidation [25]. Some trials report DHA supplementation attenuated the increase in mean arterial blood pressure [26], decreased triglyceride levels [27] as well as oral glucose tolerance [28] in adults. However, there was no recognizable improvement in cognitive decline [29].…”
Section: Role Of Dha In Adultsmentioning
confidence: 99%
“…In healthy older males, DHA supplementation was found to modulate age-related cardiovascular responses (mean and diastolic arterial blood pressure) in response to exercises utilizing autonomic nerve activity [26]. DHA supplementation lowered the triglyceride levels in both older women [30]and men [27]. In elderly patients with established Alzheimer's disease, DHA intervention is controversial [29,31,32].…”
Section: Role Of Dha In Geriatricsmentioning
confidence: 99%